(untitled) (Journal of Asian Development Studies, 2025)
Artificial intelligence (AI) has increasingly become a transformative tool in climate finance, enabling firms to enhance green investment strategies, assess carbon risk more accurately, and optimize capital allocation. This study investigated the role of AI in promoting sustainable finance by examining its impact on investment decisions, risk mitigation, and ESG evaluation. Data were collected from multiple firms employing AI-based analytics to support green financial initiatives, and analysed using descriptive statistics, frequency distributions, and comparative evaluation of AI adoption levels, green investment allocation, and carbon risk assessment accuracy. The findings indicated that firms with higher AI integration achieved more precise risk assessments, allocated capital more efficiently to sustainable projects, and demonstrated improved resilience to climate-related financial uncertainties. Despite these benefits, challenges were identified, including limitations in data quality, algorithmic bias, disparities in institutional readiness, and environmental impacts associated with energy-intensive AI computations. The study also highlighted that effective AI adoption required robust data governance, standardized ESG reporting frameworks, and employee training to maximize decision-making efficiency. Recommendations emphasized ethical implementation, regulatory guidance, and the integration of AI technologies with sustainability objectives to ensure both financial and environmental gains. Future research should explore cross-sectoral adoption, longitudinal impacts, and advanced AI methods such as reinforcement learning and blockchain-enabled analytics. Overall, the study demonstrated that AI not only strengthens analytical capabilities but also fosters strategic alignment between financial performance and environmental sustainability.